Behavioural and Psychological Symptoms in Poststroke Vascular Cognitive Impairment - Meena Gupta; Abhijit Dasgupta; Geeta Anjum Khwaja; Debashish Chowdhury; Yogesh Patidar; Amit Batra (Behavioural Neurology)
Background. Behavioural and psychological symptoms of dementia (BPSD) cause significant patient and caregiver morbidity in vascular cognitive impairment (VCI). Objectives. To study and compare the occurrence and severity of BPSD between multi-infarct dementia (MID), subcortical ischaemic vascular disease (SIVD), and strategic infarct subtypes of poststroke VCI and to evaluate the relationship of these symptoms with the severity of cognitive impairment. Methods. Sixty patients with poststroke VCI were classified into MID, SIVD, and strategic infarct subtypes. BPSD were studied by the neuropsychiatric inventory (NPI). The severity of cognitive impairment was evaluated by the clinical dementia rating scale (CDR). Results. 95% of cases had at least one neuropsychiatric symptom, with depression being the commonest, irrespective of subtype or severity of VCI. Strategic infarct patients had the lowest frequency of all symptoms. SIVD showed a higher frequency and severity of apathy and higher total NPI scores, compared to MID. Apathy and appetite disturbances occurred more commonly with increasing CDR scores. The total NPI score correlated positively with the CDR score. Conclusion. Depression was the commonest neuropsychiatric symptom in VCI. The neuropsychiatric profiles of MID and SIVD were similar. The frequency and severity of apathy and the net burden of BPSD increased with increasing cognitive impairment.